US-Russia policy hits European energy supply: The consequences of unilateral sanctions and growing market competition - Sascha Lohmann; Kirsten Westphal (Stiftung Wissenschaft und Politik (SWP), 2019)
Triggered by Russia's annexation of Crimea and military intervention in Ukraine in early 2014, the governments of the United States (US) and the Russian Federation have since been locked in a geopolitical confrontation, which is largely playing out on the economic stage. In addition to unilateral economic sanctions, the US government is focussing on the export of liquefied natural gas (LNG). In doing so, it wants to reduce not only Russian state revenues, but also European dependence on Russian energy imports. In this context, the US policy is aimed squarely at the German federal government, which was described by President Donald J. Trump as a "prisoner of Russia". The more the European-Russian energy trade is drawn into the conflict between Washington and Moscow, the more serious the consequences are likely to be for European energy supply.
Keywords: 320